Production of Canarium (Canarium indicum L) Butter with Different Sugar Concentrations - Helen Cynthia Dewi Tuhumury; Agustina Souripet; Kaleb Jodra Pattiwael (Journal of Applied Agricultural Science and Technology, 2023)
Tree nuts and groundnuts nowadays are gaining popularity due to their health benefits. Nut kernels that can be eaten raw or roasted are becoming increasingly popular in healthy diet, including canarium nut. Therefore, it should be used into a variety of food compositions, including butter, to promote a healthy diet and lifestyle. The objective of the research was to determine the exact sugar concentration in the production of canarium nut butter. A completely randomized experimental design with four levels of sugar concentrations i.e. 0%, 20%, 40%, and 60% was applied in this research. Chemical and sensory properties were analysed. Results showed that the sugar concentration of 40% was the exact concentration for producing canarium nut butter. The canarium nut butter at 40% sugar concentration had a moisture content of 17.70%, an ash content of 2.68%, a protein content of 6.19%, a fat content of 32.69%, and a reducing sugar content of 25.31%. Canarium nut butter at 40% sugar was also more liked on taste, texture, and its overall likeness; it was only slightly liked on aroma. This butter was rated as sweet, having a nutty aroma, smooth, and very easy to spread.